Project Management for the Implementation of Resource-Saving Technologies - Duan, Musen (Lesya Ukrainka Volyn National University, 2024)
The project for the implementation of resource-saving technologies is an initiative or activity aimed at developing and implementing approaches that contribute to the creation of sustainable and efficient resource use systems within the framework of resource conservation. These projects may include the introduction of technologies that ensure efficient use of resources, the use of renewable energy sources, the development of products with easily replaceable components, as well as the use of digital technologies for monitoring and optimizing resource use, stimulating innovation, and startups in this field. The main goal of such projects is to reduce the consumption of natural resources, decrease environmental pollution, and improve the economic efficiency of enterprises. This work covers the analysis of current trends in the field of resource conservation, the methodology of project management for the implementation of advanced technologies, as well as practical aspects of implementing such projects in various industries. The research includes an examination of successful project examples in this field, an assessment of their impact on the environment and economy, and recommendations for enhancing the efficiency of managing resource-saving technologies. The project also addresses the interaction between various stakeholders, such as government organizations, businesses, academic institutions, and the public, to ensure the successful implementation and dissemination of innovative solutions. An important aspect of the research is the analysis of barriers and challenges that companies may face during the implementation of resource-saving technologies, as well as the development of strategies to overcome them. The work presents recommendations for optimizing change management processes, increasing awareness and training of personnel, and creating incentives for companies implementing innovative technologies. This research will contribute to a better understanding of the mechanisms and tools necessary for the successful implementation of resource-saving technologies in contemporary conditions.
Keywords: project management; resource conservation; sustainable development; project management methodology